2019
DOI: 10.1111/jvh.12979
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric symptoms in hepatitis C patients resemble those of patients with autoimmune liver disease but are different from those in hepatitis B patients

Abstract: Chronic fatigue, mood alterations and cognitive impairment are frequent accessory symptoms of HCV-infection. Fatigue and mood alterations have also been observed in autoimmune hepatitis (AIH) and primary biliary cholangitis (PBC), but not in hepatitis B virus (HBV)-infection, thus indicating an autoimmune response as possible cause of HCV-infection associated encephalopathy. Data, however, are sparse. This study aims to prove that HCV patients feature similar to those with autoimmune liver disease but contrary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Chronic HCV infection without cirrhosis is however associated with worse quality of life and symptoms (e.g. mood disorders and fatigue) than those who do not have this infection [ 3 ]. On large cohorts of patients, it is also widely demonstrated that chronic HCV infection is accompanied by extrahepatic manifestations including lymphoproliferative disorders (e.g.…”
Section: The State Of the Artmentioning
confidence: 99%
“…Chronic HCV infection without cirrhosis is however associated with worse quality of life and symptoms (e.g. mood disorders and fatigue) than those who do not have this infection [ 3 ]. On large cohorts of patients, it is also widely demonstrated that chronic HCV infection is accompanied by extrahepatic manifestations including lymphoproliferative disorders (e.g.…”
Section: The State Of the Artmentioning
confidence: 99%
“…HCV-AND shows a profile of prevailing frontal lobe involvement characterized by disordered executive function, with impairment of working memory, processing speed, set-shifting, decision-making and verbal fluency [3][4][5][6], in association with apathy and disinhibition [7]. Dysfunction of the prefrontal cortex can also result in alexithymia, the inability to recognize and express one's feelings, thus affecting patient-reported symptoms [8].…”
Section: Introductionmentioning
confidence: 99%
“…The attentional function necessitates the complementary action of both frontal and parietal cortices, with the former involved in the targeting of a particular stimulus (selective attention), and the latter in maintaining that focus (sustained attention). In HCV-AND, sustained attention seems to be the more commonly affected subdomain [3], whereas episodic memory per se is relatively less affected, possibly owing to attentive disturbances and defective encoding strategies [3,9]. An uncommon feature is the impairment of cognitive domains related to posterior brain regions that affect constructional praxis, visuo-spatial and visuo-perceptual tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Depressive state is often encountered in patients with CLDs [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Even in CLD patients with an earlier liver fibrosis stage, depressive manifestations can be frequently found compared with healthy individuals [ 17 ]. In patients with chronic hepatitis C, depressive state, anxiety, and fatigue were demonstrated to be major psychiatric abnormalities [ 19 ].…”
Section: Introductionmentioning
confidence: 99%